Tunnel gradients and aural health criterion for train passengers. (September 2014) - Palmero, Natalia Montenegro; Vardy, Alan
An inconvenient consequence of the UIC health and safety criterion for allowable pressure changes in railway tunnels is highlighted. It is shown that the criterion limits allowable speeds in long tunnels with large changes of elevation much more than it does in equivalent tunnels with small changes in elevation. The constraint is especially strong for trains travelling uphill, but it can also exist for trains travelling downhill. Possible ways of avoiding the problem without reducing speed are considered and are found to be practicable in some cases. However, they are of uncertain suitability because they rely on exploiting a particular feature of the safety criterion in a manner that is unlikely to have been intended when it was mandated. In addition, attention is drawn to an ambiguity inherent in the application of the criterion to certain types of tunnel. Suggestions are made for simple modifications to the criterion and comparisons are made with conditions experienced routinely in commercial aviation.